(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to examine the effect of product innovation and digital marketing on purchasing decisions, with purchase intention as a mediating variable, on Wafer Tango consumers among students of the Faculty of Economics and Business, PGRI Semarang University. The method used is a quantitative approach with AMOS-based Structural Equation Modeling (SEM) analysis, involving 120 respondents. The results showed that product innovation has a significant effect on purchasing decisions, but not on purchase intention. Digital marketing has a significant effect on purchase intention and purchase decisions, both directly and indirectly. Purchase intention is proven to mediate the effect of digital marketing on purchasing decisions, but does not mediate the effect of product innovation. These findings emphasize the importance of the right digital strategy and relevant product innovation to improve purchasing decisions.